Exponential Model Versus Polynomial Model to Describe Height Growth of Balangeran (Shorea balangeran) Plant in Peat Swamp Lands (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Balangeran tree has excellent economic benefits and ecological value because the wood has a high selling price. The purpose of this study was to create exponential and polynomial models to describe the height growth of balangeran planted on peat swamp lands in Central Kalimantan, Indonesia. Research result show that exponential equation is valid to describe the height growth of balangeran plants with an accuracy of 97.02% and a coefficient of determination of 78.86%; meanwhile, the polynomial equation is also valid to describe the height growth of balangeran plants with an accuracy of 99.76% and a coefficient of determination of 98.92%.